1994
DOI: 10.1073/pnas.91.26.12589
|View full text |Cite
|
Sign up to set email alerts
|

Partially oxygenated sickled cells: sickle-shaped red cells found in circulating blood of patients with sickle cell disease.

Abstract: A previously uncharacterized type of sickled cell was found in venous blood ofpatients with sickle cell disease when blood was collected without exposure to air and fixed immediately with 1% glutaraldehyde solution equilibrated with 5% oxygen. These cells were either elongated, resembling irreversibly sickled cells (ISCs), or nonelongated, with a raisinlike shape. Both types assumed a normal discoidal shape upon full oxygenation. Since these cells exist only under partially oxygenated conditions, they are desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 18 publications
11
44
0
2
Order By: Relevance
“…First, since there was no technology to collect blood samples under physiological oxygen pressures for further studies, most RSCs were fixed in fixing solution at the time of blood collection. Second, when blood is collected by the ordinary method (Exp-blood), cells are exposed to oxygen in the needle, syringe, and Vacutainer, and most RSCs are oxygenated, causing them to assume a normal discoidal shape [1,2]. As we will describe in this paper, partial deoxygenation of once-oxygenated blood to venous oxygen pressure does not recover in vivo properties of SS cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, since there was no technology to collect blood samples under physiological oxygen pressures for further studies, most RSCs were fixed in fixing solution at the time of blood collection. Second, when blood is collected by the ordinary method (Exp-blood), cells are exposed to oxygen in the needle, syringe, and Vacutainer, and most RSCs are oxygenated, causing them to assume a normal discoidal shape [1,2]. As we will describe in this paper, partial deoxygenation of once-oxygenated blood to venous oxygen pressure does not recover in vivo properties of SS cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that venous blood samples collected from steady-state patients with sickle cell disease (SCD) under venous oxygen pressure without exposure to air (UnExp-blood) contained many reversibly sickled cells (RSCs) with blunt edges [1,2]. Although the percentage varied widely among patients (4-78%), it remained within a narrow range in individual patients during the steady state [3].…”
Section: Introductionmentioning
confidence: 99%
“…UnExp-blood was collected from the antecubital vein for routine blood tests [9,10]. To prevent in vivo cell sickling caused by stagnation of blood [11], the tourniquet was released after the needle was inserted into the vein and before the blood was drawn.…”
Section: Materials and Methods Blood Samplesmentioning
confidence: 99%
“…Although the sickled cells found in UnExp-blood had a shape similar to ISCs, most of the sickled cells were determined to be POSCs because they converted to discocytes upon exposure to air or carbon monoxide [10,19]. Blood samples collected by the standard method do not contain a large number of POSCs because they are oxygenated to discocytes by the oxygen in the volume of air in the needle, syringe, and Vacutainer [9,10]. As shown herein, although the percentage of POSCs varied widely among patients, the percentage and morphological characteristics of POSCs in individual patients were maintained in a narrow range during steady state.…”
Section: Changes In the Percentage And Morphology Of Sickled Cells Afmentioning
confidence: 99%
See 1 more Smart Citation